Adjuvant vaginal cuff brachytherapy in surgically treated endometrial carcinoma patients – in view of the recent evidence - Serkies, Krystyna; Baczkowska-Waliszewska, Zuzanna (Journal of Contemporary Brachytherapy, 2021)
Vaginal cuff brachytherapy is an essential component of adjuvant post-operative therapy in endometrial carcinoma. Brachytherapy boost, as a part of adjuvant pelvic radiotherapy, including concomitant chemoradiotherapy combined with four cycles carboplatin/paclitaxel chemotherapy, is used in early-stage high-risk and advanced stage disease. This strategy is widely accepted and recommended by international guidelines, despite the fact that combined therapy has never been verified in randomized trials. Brachytherapy alone is the adjuvant treatment of choice for many patients with early-stage endometrial cancer, with high-intermediate features, replacing external beam pelvic radiotherapy. It provides equivalent vaginal control with a lower risk of toxicity, and minimal impact on health-related quality of life. Available evidence did not demonstrate the superiority of sole vaginal brachytherapy combined with three cycles of carboplatin/paclitaxel chemotherapy, over the standard pelvic irradiation for patients with early-stage, high-intermediate-, and high-risk endometrial cancer. This article summarized the available evidence on the role of post-operative vaginal cuff brachytherapy in endometrial cancer patients. Additionally, the risk groups definition, some aspects of brachytherapy technique, and the importance of pathological and molecular risk factors for endometrial cancer risk stratification were presented. Furthermore, the role of brachytherapy according to the European Society of Gynecological Oncology/European Society for Radiotherapy and Oncology/European Society of Pathology 2021 guidelines for the management of patients with endometrial carcinoma was presented.